STUDY OF SIGNIFICANCE OF PHASE MASK IMAGE IN ACUTE STROKE PATIENTS - Nerella, Krishna Teja; Ayapaneni, Dileep Reddy; Srikonda, Surekha (MNJ (Malang Neurology Journal), 2022)
Background: Phase images contains information regarding local susceptibility changes between the tissues, which can help measure the iron and other content which changes the local field. Typically, this information is ignored before looking at console. Susceptibility weighted imaging (SWI) is a magnetic resonance (MR) technique detects an early hemorrhagic transformation within the infarct to provide insight into cerebral hemodynamics following the stroke.Objective: Significance of â€œphase mask imaging in differentiation of hemorrhage and calcificationsâ€ in acute stroke patients.Methods: An observational non-interventional study carried out on 100 patients with stroke and headache symptoms. MRI Brain Stroke Profile with FLAIR, DWI, ADC, SWAN, and Phase mask sequences, done on 3T GE MRI scanner.Results: All patients underwent MRI study with SWI sequence. Of 183 cases, 33%(n=60) patients had microbleeds, 5%(n=10) patients had granulomas, 32%(n=58) patients had arterial thrombus with infarct, 11%(n=20) patients had falx calcifications, 11%(n=20) patients had intraparenchymal haemorrhage, and 8%(n=15) patients had infarcts with haemorrhagic transformation. The sensitivity of phase imaging in the detection of calcification was 90%.Conclusion: Phase mask imaging plays an important role to detect intracranial calcifications and chronic microbleeds. Phase mask imaging acts as a supplement tool in acute stroke patients, which guides further management.